A Sociolinguistic Study: Analysis of Code-Switching in Maudy Ayunda’s Speech on Rory Asyari’s Youtube Channel - Nazwa Lasyela; Arya Legawa Amrin; Adifa Zahfa Putra Pratama; Lia Isnaniyah; Delia Oktaviana; Radithya Rifqy Rafif (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Code-switching is a common phenomenon in bilingual communication, including in digital media like YouTube podcasts. This study aims to identify and analyze the types of code-switching used by Maudy Ayunda in her YouTube podcast entitled “Maudy Ayunda: Kenapa Kita Selalu Merasa Ngga Cukup? Insecurity & Cara Berdamai dengan Diri Sendiri” Guided by Rori Asyari. This study uses a qualitative descriptive method with data in the form of speech containing code-switching. The data analysis is based on the theory of Appel and Muysken (1987) supported by Poplack's classification (1980). The results of the study show that there are three types of code-switching: tag-switching, intra-sentential switching, and inter-sentential switching. Intra-sentential switching is the most dominant type used, followed by inter-sentential switching and tag-switching. These findings show that the use of code-switching in podcasts functions as a communication strategy that helps speakers convey ideas more naturally and effectively in the context of bilingual digital communication.